Strategi Pendampingan Public Speaking Santri melalui Kegiatan Muhadharah di Pondok Pesantren Nurul Huda Al-Muniriyyah - Sa’diyah, Umi Lailatus; Jauhari, Minan (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2023)
To achieve success in the skills of the santri, it can be through muhadharah assistance, which requires continuous training, especially among supporters and executors (da'i) and generally among the younger generations. One of them is by holding assistance in an effort to study and develop students' skills in speaking and interacting in public. Research objectives: 1.) To explain the strategies for assisting public speaking students at the Nurul Huda Al-Muniriyyah Islamic Boarding School. 2.) To explain the activities of muhadharah activities as a public speaking strategy for students at the Nurul Huda Al-Muniriyyah Islamic Boarding School. This study uses a descriptive qualitative research method. The data collection techniques using interviews, observation and documentation. The results of the study: the public speaking mentoring strategy can be carried out with mentoring, namely with the aim of the muhadharah supervisor being able to guide the students in practicing before appearing at the muhadharah activity, then holding a speech competition with the aim of training the mentality of the students in public speaking (public speaking). In order for students' public speaking to be better, a muhadharah activity is held once a month, namely on Monday nights and Tuesdays. Muhadharah activities begin with the MC, reciting the holy Qur'an, reading sholawat, speeches and ending with prayers. Through these activities, students will be better trained and able to speak in public.